I want my hat back - Klassen, J. (Somerville, Mass. : Candlewick Press, 2011)
A bear almost gives up his search for his missing hat until he remembers something important.
Keywords: Bears -- Fiction; Hats -- Fiction; Lost and found possessions -- Fiction; Bears -- Fiction; Hats -- Fiction; Lost and found possessions -- Fiction